Case Report on Perihilar Cholangiocarcinoma - Aravind, M.; T, Immanuvel.; Gk , Parigodson.; Karthickeyan, K.; Sundaram, P. Shanmuga; Dheenadhayalan, M.; Sri, M.K. Sundar (Journal of Neonatal Surgery, 2025)
A 61 years old female patient was a known case of hilar cholangiocarcinoma type 3A status post percutaneous transhepatic drainage + metal stenting done on 2025 on cyclical antibiotics. She is planned for plan for right hepatectomy + CBD excision + Hep J. Now been admitted in hospital. Past history of evaluated for jaundice + yellowish color of urine in march 2025. History of CAM intake for skin hyperpigmentation. History of weight loss +. She was diagnosed with hilar cholangiocarcinoma type 3A. Past surgery status post percutaneous transhepatic biliary drainage + metal stent in febuary 2025. Procedure done right hepatectomy + CBD excision + Hep J done on May 2025. She was started with prophylactic antibiotics and analgesic. She was hemodynamically stable, afebrile surgical wound healing with primary intentions.